Three-dimensional finite-difference time-domain simulation on coaxial transmission line for broadband dielectric characterization - Noor Ahmad, Sarimah (2014)
In this work, a part of a coaxial transmission line is used as a sample holder where the propagation of electromagnetic waves in the range of 500 MHz is studied using three-dimensional (3D) finite-difference time domain (FDTD) method. This study presents the results from the numerical simulations of electromagnetic waves in a mixture of dielectric materials. The effective relative permittivity of the mixture is calculated by recording one of the electric field components (Ey) of the transmitted and reflected electromagnetic pulses in the transmission line. The complex frequency spectra of these time-domain signals are then obtained by taking the Fourier transforms of the respective signals. These spectra are then used to calculate the complex transmission and reflection coefficients for the sample. The analysis of raw data is performed using open source package, GNU Octave. Finally a numerical procedure is developed to convert the raw data into an effective dielectric property of the mixture of materials. The influence of water contents on dielectric properties is studied using samples made from different mixtures of soil, water, and air. The results show that the effective dielectric permittivities of the mixtures are highly dependent on the soil’s moisture content. Strong frequency dependence in the dielectric properties is observed especially at the low end of frequency range which can be attributed to the presence of the DC conductivity of water (5